SUBSTITUSI TEPUNG SORGUM PADA PEMBUATAN COOKIES RED VELVET - Sutriyati Purwati, Arif Sorya Wicaksana (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to 1) find the right recipe in the manufacture of red velvet Cookies grain sorghum flour substitution. 2) to investigate public acceptance of Cookies red velvet. 3) find the nutritional information on Cookies red velvet. The method used is the R & D with the 4D model is Define, Design, Development, and Disseminate. Samples were 30 semi-trained panelists to test a limited scale A and 80 untrained panelists for wide scale acceptance testing. The research result got the right recipe for the substitution of 60% of the sorghum flour made with the creaming method and packed with jars of mica. Public acceptance test results received proceeds of 3.4 to aromas and flavors as well as 3.5 for color, texture, and overall value. It can be concluded that red velvet sorghum flour Cookies can be accepted by society very well. While the test results show the results A limited scale in terms of color, aroma, texture, flavor and overall more than 0.05. If P values less than 0.05, then the control and development were not significantly different and acceptable product. The test results showed proximate .... Keywords: Cookies red velvet, Formula, Sorgum flour